2012
DOI: 10.1021/jo301425c
|View full text |Cite
|
Sign up to set email alerts
|

Formal Total Synthesis of (+)-Neopeltolide

Abstract: This paper describes the formal total synthesis of (+)-neopeltolide, a cytotoxic macrolide isolated from the marine sponge Neopeltidae. The key features of the synthesis include an asymmetric Evans alkylation to fix the C9-methyl center, Jacobsen hydrolytic kinetic resolution of terminal epoxides followed by their regioselective opening to fix the stereocenters at the C11 and C13 positions, respectively, a Pd-catalyzed oxa-Michael reaction to construct the tetrahydropyran ring, and Yamaguchi macrolactonization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 43 publications
(28 reference statements)
0
10
0
Order By: Relevance
“… 65 , 66 There have been several syntheses of 27 since its isolation and numerous analogs have been produced for SAR studies. 67 , 68 , 69 , 70 Most notably, Fuwa and coworkers developed (-)-8,9-dehydroneopeltolide ( 28 ), an analog which was more potent against A549 (0.5 nM) cells, and maintained activity against MCF-7 (33 nM) and P388 (0.72 nM) compared to the parent macrolide (IC 50 values of 1.6, 19 and 0.50 nM respectively). 71 29 is a further structurally simplified analog by Fuwa et al which showed general retention of activity when tested against A549 cells (IC 50 = 43.9 nM) while noticeably reducing step count for a potent cancer cell line inhibitor while identifying tolerate areas for structural modification in future SAR studies.…”
Section: Natural Products Which Have Benefited From Analog Developmenmentioning
confidence: 99%
“… 65 , 66 There have been several syntheses of 27 since its isolation and numerous analogs have been produced for SAR studies. 67 , 68 , 69 , 70 Most notably, Fuwa and coworkers developed (-)-8,9-dehydroneopeltolide ( 28 ), an analog which was more potent against A549 (0.5 nM) cells, and maintained activity against MCF-7 (33 nM) and P388 (0.72 nM) compared to the parent macrolide (IC 50 values of 1.6, 19 and 0.50 nM respectively). 71 29 is a further structurally simplified analog by Fuwa et al which showed general retention of activity when tested against A549 cells (IC 50 = 43.9 nM) while noticeably reducing step count for a potent cancer cell line inhibitor while identifying tolerate areas for structural modification in future SAR studies.…”
Section: Natural Products Which Have Benefited From Analog Developmenmentioning
confidence: 99%
“…Subhash Ghosh and co-workers from Indian Institute of Chemical Technology reported a formal synthesis of neopeltolide, featuring a palladium-catalyzed intramolecular oxa-Michael addition for constructing the tetrahydropyran substructure [ 55 ]. Another feature of the Subhash Ghosh synthesis is the use of Jacobsen hydrolytic kinetic resolution methodology [ 155 ] for controlling the C11 and C13 stereogenic centers.…”
Section: Synthesis Of Tetrahydropyrans Via Intramolecular Oxa-michmentioning
confidence: 99%
“…However, the mode-of-action of this natural product have not been fully elucidated. The intriguing structure and potent biological activities of neopeltolide have attracted considerable attention from the synthetic community, and twenty total and formal syntheses of this natural product have been reported so far [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Furthermore, several groups have reported the structure-activity relationships of neopeltolide by evaluating the antiproliferative activity of synthetic analogues against cancer cells [ 34 , 43 , 47 , 56 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was then subjected to palladium-catalyzed oxy-Michael reaction to form two diastereomers 96a cis-C7 (R) and 96b trans-C7 (S) in 48% yield and 12% yield respectively (Scheme 23). 28 Ketone 97 was the delivered in a further 2 steps.…”
Section: Michael Reactionsmentioning
confidence: 99%